Вплив Великого терору 1936-1938 років на діяльність ІІІ Інтернаціоналу: історіографія проблеми - Римар, І.; Черевко, О. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2019)
У статті аналізуються наукові розвідки зарубіжних та вітчизняних
дослідників, присвячені вивченню причин, витоків, перебігу Великого
терору в СРСР (1936–1938 рр.), його впливу на діяльність ІІІ Інтернаціоналу та національних секцій. Окрема увага приділена висвітленню в
науковій літературі ролі керівництва НКВС та особисто Й. Сталіна в
цьому процесі. У контексті проблеми репресій та Великого терору
схарактеризовані комплексні наукові дослідження, в яких розглядаються
механізми й засоби реалізації терору та репресій проти функціонерів
Секретаріату ІІІ Інтернаціоналу та національних секцій. Здійснено
спробу узагальнити погляди дослідників проблеми, виявити їхнє спільне
бачення та найбільш дискусійні питання. The article analyzes scientific investigations of foreign and domestic
researchers devoted to the causes, origins, ways and means of the Great Terror
realization in the USSR (1936–1938), its influence on the activities of the Third
International and the subsequent destiny of its leaders. Particular attention is
paid to the role of the NKVD leadership and J. Stalin personally in the process.
In the context of the problem of repression and the Great Terror, complex
scientific researches are considered. It also examines the mechanisms and
means of realization of terror and repression, especially on the territory of the
USSR, against political opponents of J. Stalin, national minorities, functionaries
of the central apparatus of the III International, national sections.
Considerable attention is paid to the analysis of the Soviet archives published
in the first half of the 1990s and the documents (that declassified in 2015) of
the Sectoral Archive of the Security Service of Ukraine that help to rethink the
phenomenon of the Great Terror.
Analyzing the scientific investigations about repression at the Comintern, it
was concluded that, according to the researchers, it is advisable to consider
the III International both the agent, the instrument and the victim of terror.
That is given the simultaneous dependence of repression in the USSR and the
Comintern on J. Stalin, the Politburo, the Central Bureau,) and the NKVD,
which ultimately resulted into horrific consequences for both the Soviet Union
and the Third International. An attempt was made to summarize the views of
the problem researchers, to identify their shared visions and the most
debatable questions about the problem studied.